Boris Lurie & Wolf Vostell vernichten, vergessen, verdrängen : destroy, forget, suppress - Reifenscheid, Beate 1961-; Bergmann, Rudij 1943-; Christians-Bernsee, Annemone 1981-; Elantkowski, Jan; Gillen, Eckhart 1947-; Groenteman, Bram; John, Philipp N.; Weibel, Peter 1944-2023 (Silvana Editoriale, 2023)
After the Second World War and the Shoah, only few artistic positions came to terms with what had happened, and in only few countries was a social reappraisal even initiated. In many cases, forgetting, repression or pure consumerism prevailed. In the years between the Cold War, the Vietnam War, the Cuban Missile Crisis and the economic miracle, the artists Boris Lurie and Wolf Vostell played a central role: the former in an attitude of absolute negation with his No!Art and the latter with happenings and works that also incorporated the new media of the time. The publication traces with eight contributions this era of the post-war decades up to the 1990s and was the basis for the academic symposium of the same name.
Impressum: Dieser Katalog erscheint anlässlich des Symposiums: "Vernichten, vergessen verdrängen". Symposium im Ludwig Museum Koblenz und in der Universität Koblenz-Landau, 30. November 2022 - 02. Dezember 2022
Keywords: Lurie, Boris -- 1924-2008; Vostell, Wolf -- 1932-1998; No!art -- Künstlergruppe; Rezeption; Judenvernichtung; No! Art; Nationalsozialismus; Kunst; Konferenzschrift -- 2022 -- Koblenz